"Desenvolvimento e avaliação de matriz, filtrante e desfluoretadora, constituída por óxido de cério suportado em carvão ativado proveniente de casca de coco (Cocos nucifera L.) para áreas de desertificação" - Santos, Carlos Christiano Lima dos (2021)
This study aims to present an accessible and sustainable proposal for development and evaluation of a activated carbon/CeO2 filter matrix for water defluoridation, with potential application in Brazilian regions and abroad with high fluorosis (dental and skeletal) incidence. Using a soft chemistry process, microwave assisted hydrothermal rout, cerium (VI) oxide nanostructures (ceria, CeO2) and its composites (activated carbon/CeO2 with 0%, 1%, 10% and 20% of CeO2) were prepared, using coconut (Cocos nucifera L.), from using coconut residue (Cocos nucifera L.), from the agribusiness in the interior of Paraiba. All synthesis, were proceeded at 120 °C, with different time intervals (1, 5, 15, 30 and 60 minutes, for the CeO2 obtention; and 30 minutes for composites – activated carbon/ CeO2). The structural, thermodynamic, morphological and adsorptive (fluorine) properties, were analyzed by X-ray diffraction (XRD), Energy-dispersive X-ray spectroscopy (EDX), Infrared spectroscopy (IR), Thermogravimetric analysis (TGA), BET adsorption method, high resolution transmission electron microscopy (HR-TEM), high resolution scanning electron microscope (HR-SEM), respectively. The phase of the cerium oxide was determined by XRD analysis with planes ((1 1 1), (2 0 0), (0 2 2), (3 1 1), (2 2 2) and (4 0 0), in accordance with the cards JCPDS 34-0394), and the presence of the composite deposition was confirmed by EDX analysis. BET results showed for the best sample a surface area of (261 m2. g-1) for ceria particles, synthesized for 5 minutes. Microscopic analyzes (HR-SEM and HR-TEM) confirmed these results, presenting particle clusters of the order of 5nm, which justified its use for the composites production. Analyzes of fluoride concentration (direct and indirect methods), in composites obtaining, on a laboratory scale, were performed in triplicate with mean ± deviation and Tukey test with significant differences (p <0.05) between, and its results showed fluorine ions adsorption only in the composite with higher cerium oxide (IV) concentrations (10 to 20 %). As the statistical analysis of this adsorbing materials showed no significant difference regarding the catalysis of fluorine ions, the composite with 10% concentration of the oxide, for the different water matrices used (7 and 23 ppm), was chosen as the most sustainable and economical proposal to this end. From these results a viable and sustainable proposal, of waste resignification from local agribusiness by using coconut biomass, as raw material for the production of defluoridation matrix, that can be applied to the reduction of fluorine in springs of deserted areas.